Формирование участников логистической сети цепочек поставок при стратегическом управлении - Годлевский, Михаил Дмитриевич; Станкевич, А. А.; Чернявская, Л. С.; Рубин, Э. Е. (НТУ "ХПИ", 2013)
There have been proposed the approach to the formation of the participants in the logistics supply chain strategic management. In the method is based on the expert approach to the evaluation of alternatives. The mathematical model for decision making.
Keywords: логистика; подход экспертный; альтернатива; модель математическая